Five Macro Trends and Their Impacts on Higher Education - Mark Putnam (Academic Chairpersons Conference Proceedings, 2016)
understanding marketplace demographics, piecing together economic puzzles, processing governance and the legitimacy of leadership, developing technology and the learner, and recognizing ambiguities of institutions and society.
Keywords: Macro Trends